Fundamentals of terminology in lower urinary tract function. (15th August 2018) - Drake, Marcus J.
Abstract : Aims: To summarize basic definitions in the International Continence Society (ICS) Standardization of Terminology in lower urinary tract (LUT) function and their application. Methods: Fundamental terminology in the ICS Standardization of Terminology LUT Function was identified and summarized. Results: Evaluation of LUT requires appreciation of symptoms, signs and urodynamic observations. Symptoms are categorized according to their occurrence during the micturition cycle into storage symptoms (eg, increased daytime frequency [IDF], urgency, nocturia, or incontinence) or voiding and post‐voiding symptoms (eg, slow stream or post micturition dribbling). Several problems may be present, giving rise to symptom syndromes, notably overactive bladder (during the storage phase) or underactive bladder (during the voiding phase). Signs may be derived from a bladder diary or may be elicited on physical examination. Urodynamic observations may be made by assessing flow rate, and this is combined with pressure measurement when undertaking filling cystometry and pressure flow studies. Key elements of flow and pressure measurement are described. Conclusions: The review provides a succinct summary of symptoms, signs, and urodynamic observations as set out in the ICS Standard on LUT Function.